Osseointegration and Remodeling of Mineralized Bone Graft Are Negatively Impacted by Prior Treatment with Bisphosphonates. (5th October 2022) - Cohen, D. Joshua; Lohmann, Christoph H.; Scott, Kayla M.; Olson, Lucas C.; Boyan, Barbara D.; Schwartz, Zvi
Abstract : Background: Bisphosphonates limit resorption by inhibiting osteoclast formation and activation. They are removed during preparation of demineralized bone matrix (DBM) particles, but it is not known if osteogenesis and incorporation of mineralized bone allografts from patients treated with oral bisphosphonates are affected in vivo. Methods: Human block allografts from 3 bisphosphonate-treated donors and 3 age and sex-matched control donors who had not received bisphosphonates were obtained (Musculoskeletal Transplant Foundation); one-half from each donor was demineralized. In the first study, 3 × 2-mm mineralized and demineralized cylindrical grafts were implanted bilaterally in the femoral metaphysis of 56 rats. In the second study, samples from each group were pooled, prepared as particles, and implanted bilaterally in the femoral marrow canal of 24 rats. Osseointegration, defined as native bone in contact with allograft, was assessed at 10 weeks by micro-computed tomography (CT) and histomorphometry. Results: Micro-CT showed greater bone volume in sites treated with demineralized samples compared with the control mineralized and bisphosphonate-exposed mineralized samples. More new bone was generated along the cortical-endosteal interface compared with mineralized samples. Histology showed significantly less new bone in contact with the mineralized bisphosphonate-exposed allograft (10.4%) compared with mineralized samples that did not receive bisphosphonates (22.8%) and demineralized samples (31.7% and 42.8%). A gap was observed between native bone and allograft in the bisphosphonate-exposed mineralized samples (0.50 mm 2 ). The gap area was significantly greater compared with mineralized samples that did not receive bisphosphonates (0.16 mm 2 ) and demineralized samples (0.10 and 0.03 mm 2 ). Conclusions: Mineralized allografts were osseointegrated, but not remodeled or replaced by living bone, preventing full regeneration of the bone defect. Prior treatment of the donor with bisphosphonates affected osteogenesis, preventing osteointegration and remodeling of the allograft into the regenerating bone. Clinical Relevance: Clinical use of mineralized allografts from patients who had received bisphosphonate therapy needs to be evaluated; in this animal model, such grafts were not integrated into the host bone or remodeled, and full regeneration of the bone defects was prevented.